Plasmodium falciparum coronin organizes arrays of parallel actin filaments potentially guiding directional motility in invasive malaria parasites - Olshina, Maya A.; Angrisano, Fiona; Marapana, Danushka S.; Riglar, David T.; Bane, Kartik; Wong, Wilson; Catimel, Bruno; Yin, Meng-Xin; Holmes, Andrew B.; Frischknecht, Friedrich; Kovar, David R.; Baum, Jake (Malaria journal, 2015)
Gliding motility in Plasmodium parasites, the aetiological agents of malaria disease, is mediated by an actomyosin motor anchored in the outer pellicle of the motile cell. Effective motility is dependent on a parasite myosin motor and turnover of dynamic parasite actin filaments. To date, however, the basis for directional motility is not known. Whilst myosin is very likely orientated as a result of its anchorage within the parasite, how actin filaments are orientated to facilitate directional force generation remains unexplained. In addition, recent evidence has questioned the linkage between actin filaments and secreted surface antigens leaving the way by which motor force is transmitted to the extracellular milieu unknown. Malaria parasites possess a markedly reduced repertoire of actin regulators, among which few are predicted to interact with filamentous (F)-actin directly. One of these, PF3D7_1251200, shows strong homology to the coronin family of actin-filament binding proteins, herein referred to as PfCoronin.